2004
DOI: 10.1034/j.1600-0579.2003.00324.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Association amongst factors thought to be important by instructors in dental education and perceived effectiveness of these instructors by students

Abstract: It is hypothesised that dental educators have perceptions of their roles as effective teachers. It is expected that subject matter expertise would be amongst the components of such personal philosophies of education, but it is unclear whether faculty member self-perceptions carry over into student ratings of instructors' effectiveness. A 20-item survey of 'Teaching Characteristics' was completed by 86% of full-time and 64% of the part-time faculty members at the University of the Pacific. Respondents distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 16 publications
4
36
0
3
Order By: Relevance
“…These treatments demand long clinical hours due to the complexity of the procedures involved unlike other restorative dental procedures. Chambers suggested that ideally students should enter dental clinic with acceptable skill levels. Clinical environment should provide good learning environment for both clinical procedures and performance settings .…”
Section: Discussionsupporting
confidence: 90%
“…These treatments demand long clinical hours due to the complexity of the procedures involved unlike other restorative dental procedures. Chambers suggested that ideally students should enter dental clinic with acceptable skill levels. Clinical environment should provide good learning environment for both clinical procedures and performance settings .…”
Section: Discussionsupporting
confidence: 90%
“…A more recent study showed that clinical instructors have different ideas about what makes a good teacher than do students. Students found expertise not as important as enthusiasm and communications skills . Present study results concur with these findings and also indicated a need for development of teacher curriculum and supervisory practices that would include enhancement of mentoring skills.…”
Section: Discussionsupporting
confidence: 85%
“…Although there is a wealth of educational literature on effective classroom teaching, there appears to be far fewer studies that focus on clinical teaching effectiveness (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although there is a wealth of educational literature on effective classroom teaching, there appears to be far fewer studies that focus on clinical teaching effectiveness (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%